A reactivity-based [18F]FDG probe for in vivo formaldehyde imaging using positron emission tomography. Issue 8 (25th May 2016) - Liu, Wei; Truillet, Charles; Flavell, Robert R.; Brewer, Thomas F.; Evans, Michael J.; Wilson, David M.; Chang, Christopher J.
Abstract : We present an aza-Cope-based reactivity probe for imaging formaldehyde in vivo using positron emission tomography. Abstract : Formaldehyde (FA) is a reactive carbonyl species (RCS) that plays a broad spectrum of roles in epigenetics, toxicology, and progression of diseases ranging from cancer to diabetes to neurodegeneration, motivating the development of translatable technologies for FA imaging. Here we report formaldehyde-caged-[ 18 F]fluorodeoxyglucose-1 ([ 18 F]FAC-FDG-1), an aza-Cope-based reactivity probe for in vivo FA imaging using positron emission tomography (PET). [ 18 F]FAC-FDG-1 reacts selectively with FA over potentially competing analytes to generate [ 18 F]FDG, allowing its FA-dependent uptake and retention in cell culture as well as in animal models. The relative uptake of [ 18 F]FAC-FDG-1 was evaluated using FA-treated PC3 prostate cancer and U87-MG glioblastoma cells demonstrating a dose-dependent response to exogenously added FA. Moreover, [ 18 F]FAC-FDG-1 is capable of FA detection in vivo using a PC3 tumor xenograft model. In addition to providing a unique tool for monitoring FA in living animals, these data establish a general approach for translatable detection of FA and other reactive biological analytes in vivo by exploiting the widely-available clinical [ 18 F]FDG tracer as a masked aldehyde that can be caged by analyte-responsive triggers.